Simulation and analysis of cellular internalization pathways and membrane perturbation for graphene nanosheets - Mao, Jian; Guo, Ruohai; Yan, Li-Tang (Biomaterials, 2014)
Clarifying the mechanisms of cellular interactions of graphene family nanomaterials is an urgent issue to the development of guidelines for safer biomedical applications and to the evaluation of health and environment impacts. By combining large-scale computer simulations, theoretical analysis, and experimental discussions, here we present a systematic study on the interactions of graphene nanosheets having various oxidization degrees with a model lipid bilayer membrane. In the mesoscopic simulations, we investigate the detailed translocation pathways of these materials across a 56 × 56 nm2 membrane patch which allows us to fully consider the role of membrane perturbation during this process. A phase diagram regarding the transmembrane translocation mechanisms of graphene nanosheets is thereby obtained in the space of oxidization degree and particle size. Then, we propose a theoretical approach to analyze the effects of various initial equilibrium states of graphene nanosheets with membrane on their following cellular uptake process. Finally, we demonstrate that the simulation and theoretical results reproduce some important experimental findings towards the mechanisms of cytotoxicity and antibacterial activity of graphene materials. These results not only provide new insight into the cellular internalization mechanism of graphene-based nanomaterials but also offer fundamental understanding on their physicochemical properties which can be precisely tailored for safer biomedical and environment applications.